The Role of Inflation and Interest Rates in Influencing the Performance of Sharia Stocks - Akmal, Denara; Aini, Asti; Evania, Khalisa Erlinda; Aguspriyani, Yani; Juheti, Juheti (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
This study aims to investigate the role of inflation and interest rates in influencing the performance of Sharia-leading stocks, especially those included in the Jakarta Islamic Index (JII). Globally, Indonesia has become the seventh leading center of sharia finance. Global challenges and fluctuating domestic economic conditions have suppressed the performance of sharia stocks since 2023. Sharia stocks' unique characteristics distinguish them from conventional capital markets, creating a research gap in understanding the factors influencing them. This study used a quantitative approach and the data was taken from the period January 2020 to July 2024. The result of the t-test found that the t-count value is -0.229, which is greater than the t-table (-0.229 <1.674). A negative value indicates that inflation has a negative effect in the opposite direction to the performance of sharia stocks. Likewise, the interest rates are known that the t-count value of -0.841 is smaller than the t-table (1.674) or it can be stated that -0.81 < 1.674. That means in this context there is no statistically significant effect of the interest rate variable on the performance of Islamic stocks in the JII. The results of simultaneous testing showed that the F-count is 0.535, smaller than the F-table value of 3.47 which means inflation and interest rates did not significantly influence the performance of Sharia stocks. These findings are interesting considering that both variables are usually considered the main factors influencing the stock market in general. This indicates that sharia stocks in Jakarta Islamic Index (JII) have their own mechanism for dealing with macroeconomic changes, so their movement is not entirely dependent on fluctuations in inflation and interest rates.